1989
DOI: 10.1111/j.1471-4159.1989.tb01843.x
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and Pharmacological Properties of the GABAA/ Benzodiazepine/Chloride Ionophore Receptor Complex in the Brain of the Fish Anguilla anguilla

Abstract: In the present study, we characterized the distribution and the pharmacological properties of the different components of the GABAA receptor complex in the brain of the eel (Anguilla anguilla). Benzodiazepine recognition sites labeled "in vitro" with [3H]flunitrazepam ([3H]FNT) were present in highest concentration in the optic lobe and in lowest concentration in the medulla oblongata and spinal cord. A similar distribution was observed in the density of gamma-[3H]aminobutyric acid ([3H]GABA) binding sites. GA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

1990
1990
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 38 publications
2
10
0
Order By: Relevance
“…Species differences in biochemical and pharmacological properties of the brain GABA/benzodiazepine/C1-channel receptor complex have already been documented in several studies (Rauh etal., 1990;Mann and Enna, 1980;Corda et al, 1989). These studies almost exclusively demonstrated differences between invertebrates and vertebrates suggesting that this receptor complex has been conserved over vertebrate evolution.…”
Section: Discussionmentioning
confidence: 94%
“…Species differences in biochemical and pharmacological properties of the brain GABA/benzodiazepine/C1-channel receptor complex have already been documented in several studies (Rauh etal., 1990;Mann and Enna, 1980;Corda et al, 1989). These studies almost exclusively demonstrated differences between invertebrates and vertebrates suggesting that this receptor complex has been conserved over vertebrate evolution.…”
Section: Discussionmentioning
confidence: 94%
“…The fish as member of the lower vertebrates was reported to have lower affinity in its GABA A receptor towards TBPS. Corda et al, (1989) found that the eel brain GABA A receptor has relatively lower binding affinity with TBPS. They concluded that the mammalian species brain is generally characterized by the high binding affinity of TBPS with in their GABA A receptor.…”
Section: Rat Cowmentioning
confidence: 98%
“…Only one population of benzodiazepine recognition sites was found in the whole eel brain. In particular, Corda et al (1989) described the highest concentration of BZ binding sites in the optic lobe and the lowest in the medulla oblongata and spinal cord. In the Atlantic salmon, immunocytochemical investigations, using a monoclonal antibody against the GABA-receptor b 2 /b 3 subunits, revealed immunoreactivity in all parts of the brain (Anzelius et al, 1995).…”
Section: Introductionmentioning
confidence: 98%
“…Subsequently, the distribution and pharmacological properties of the different components of the GABA A receptor complex in the brain of the eel were extensively investigated (Corda et al, 1989). Only one population of benzodiazepine recognition sites was found in the whole eel brain.…”
Section: Introductionmentioning
confidence: 99%